Mongolia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper and Statistical Appendix analyzes growth and recovery in Mongolia during transition. The paper describes the major sources of economic growth in Mongolia since the early 1980s in the context of a basic growth accounting framework. It discusses Mongolia's post-transition growth performance relative to other transition countries. This paper also summarizes the main weaknesses of the existing national accounts statistics and reviews the recent developments and prospects for the main components of GDP.